Lumbar Hernia Post Latissimus Dorsi Myocutaneous Flap Reconstruction for Breast - Panja, Soumyajyoti; Dutta, Tushar; Biswas, Gautam (Indian Journal of Plastic Surgery, 2025)
We report a case of lumbar hernia in a patient with carcinoma in right breast who underwent mastectomy and reconstruction with a latissimus dorsi myocutaneous flap. Although rare, the diagnosis of lumbar hernia should be kept in mind in cases where latissimus dorsi myocutaneous flap is done to differentiate it from seroma (where aspiration is a form of management) and avoid potential complications such as bowel perforation. Treatment options are individualized, and can range from fascia closure, mesh reinforcement to minimally invasive laparoscopic and endoscopic techniques.
Keywords: latissimus dorsi flap; lumbar hernia